Action learning at work / edited by Alan Mumford - Mumford, Alan (Gower, 1997)
Thirty-four articles and papers on the Action Learning approach to management are collated by the author in this book. A wide range of issues is addressed, from underlying philosophy to evaluation to learning the process itself.